Substrate integrated waveguide filter on LCP substrate at 94 GHz. Issue 3 (March 2016) - Zhang, Yifei; Shi, Shouyuan; Martin, Richard D.; Prather, Dennis W.
ABSTRACT: In this paper we present a substrate integrated waveguide (SIW) filter on a thin film liquid crystal polymer (LCP) substrate at 94 GHz. The proposed filter consists of two cascaded SIW cavities coupled through an iris window, and is fed by microstrip lines. These two cavities are constructed using twenty four vias. The full‐wave simulation predicts the proposed filter has a pass band of 8% centered at 94 GHz. To validate our design, low‐loss and low‐reflection CBCPW probe pads without ground‐connected vias were also designed to integrate with the microstrip lines for probing. The devices were fabricated on a large LCP panel by using commercial state‐of‐the‐art large‐scale circuit printing technologies. The measured spectrum responses of the second‐ordered SIW filter are in good agreement with the simulated ones, and the total insertion loss is below 2.6 dB at 94 GHz with two feeding CBCPW pads. © 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:577–580, 2016